2021
DOI: 10.1152/ajpendo.00474.2020
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: influence of phosphate and magnesium, moderated by vitamin D, on energy (ATP) metabolism and on severity of COVID-19

Abstract: The use of vitamin D to reduce the severity of COVID-19 complications is receiving considerable attention, backed by encouraging data. Its purported mode of action is as an immune modulator. Vitamin D, however, also affects metabolism of phosphate and Mg, which may well play a critical role in SARS-CoV-2 pathogenesis. SARS-CoV-2 may induce a cytokine storm that drains ATP whose regeneration requires phosphate and Mg. These minerals, however, are often deficient in conditions that predispose people to severe CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 69 publications
0
67
0
1
Order By: Relevance
“…We found interestingly that the pathways related to viral and antiviral activities identified in the plasma of severe patient were both enhanced in the blood cells of COVID-19 patients, indicating the viral replication was active in blood cells and the immune system of blood cells were intensively involved in the viral defense. Meanwhile, the genes identified in plasma DNA consistently downregulated in lung cells with SARS-CoV-2 infection were predominantly enriched in the ATP synthesis pathways, suggesting the decreased ATP and energy reserves due to the lung injury during SARS-COV-2 infection, which has been evidenced to be closely related to the severe COVID-19 symptoms (Patel and Sriram, 2009;van Kempen and Deixler, 2020). These findings were further clearly observed in another sample set.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We found interestingly that the pathways related to viral and antiviral activities identified in the plasma of severe patient were both enhanced in the blood cells of COVID-19 patients, indicating the viral replication was active in blood cells and the immune system of blood cells were intensively involved in the viral defense. Meanwhile, the genes identified in plasma DNA consistently downregulated in lung cells with SARS-CoV-2 infection were predominantly enriched in the ATP synthesis pathways, suggesting the decreased ATP and energy reserves due to the lung injury during SARS-COV-2 infection, which has been evidenced to be closely related to the severe COVID-19 symptoms (Patel and Sriram, 2009;van Kempen and Deixler, 2020). These findings were further clearly observed in another sample set.…”
Section: Discussionmentioning
confidence: 53%
“…In the meantime, we found that the genes downregulated in both plasma and lung cells were mostly located in the mRNA and RNA metabolic pathways, as well as the adenosine triphosphate (ATP) synthesis during cellular respiration (Figure 5C), which reflected the severe injury of lung tissue during the SARS-CoV-2 infection. Importantly, it has been reported that people with low ATP and low energy reserves were more likely to develop severe COVID-19 symptoms (Patel and Sriram, 2009;van Kempen and Deixler, 2020), such as a cytokine storm and ARD since the depletion of intracellular ATP may cause cell death by necrosis and membrane instability, leading to the release of ATP into extracellular space (Le et al, 2019), which would over-activate the immune system (Iyer et al, 2009) and result in these severe consequences (Trautmann, 2009;Nomura et al, 2015;Kouhpayeh et al, 2020). Whereas, the pathways enriching the upregulated genes in lung cells were mainly involved in RNA splicing, segmentation, regulation of nucleocytoplasmic transport, somite development, and regulation of RNA export from nucleus (Figure 5D).…”
Section: Tss Coverage Profile In Plasma Reveals the Tissue-specific Expression Patternmentioning
confidence: 99%
“…Additionally, magnesium is important in the activation of vitamin D. Therefore, taking into account that magnesium and vitamin D are essentials for adequate immune function, a deficiency in either could contribute to cytokine storm in COVID-19 infection. Consequently, the supplementation with magnesium would be an attractive strategy for the prevention and treatment of COVID-19, especially in populations at risk [ 199 , 200 ].…”
Section: Contribution Of Micronutrients To the Therapy Of Oxidative/inflammatory Diseases Through Their Mitochondrial Actionsmentioning
confidence: 99%
“…В клиническом исследовании показано, что уровни фолатов в сыворотке крови, зависящие от В 12 , ассоциированы с тяжестью стеатогепатита (n = 200) [29]. Установлена взаимосвязь между уровнем витамина B 12 в сыворотке крови и выраженностью неалкогольной жировой болезни печени [30], а также положительные эффекты смеси витаминов D 3 , В 12 и магния на функцию почек [31].…”
Section: противодействие поражениям печени и почекunclassified